Inventory of Aquatic Insects as Bioindicators of Pollution in Sosongian Watershed, South Minahasa District. - Roesli, Sara H.; Kaligis, James B.; Watung, Jackson F. (Jurnal Agroekoteknologi Terapan (Applied Agroecotechnology Journal), 2025)
Abstract. Over time, human activities have increased, resulting in potentially polluted rivers. Variations in aquatic insect populations in freshwater ecosystems can indicate the possibility of pollution. This study aims to inventory and identify various types of aquatic insects as bioindicators of pollution in the Sosongian watershed, South Minahasa Regency. Sampling was conducted using kick sampling, hand picking, and sweeping techniques at three Sosongian river stations. Identification of aquatic insects using identification key McCafferty (1981); Morse et al (1994); Yule & Hoi sen (2004); Nebois (1991); Carver (1991).  The results found six orders and 21 families of aquatic insects. Key Words: Inventory, Aquatic Insects, Pollution Bioindicators Abstrak. Seiring berjalannya waktu, aktivitas manusia terus meningkat dan mengakibatkan sungai berpotensi tercemar. Variasi populasi serangga air yang ada dalam ekosistem air tawar bisa mengindikasikan kemungkinan pencemaran terjadi. Penelitian ini bertujuan untuk menginventarisasi dan mengidentifikasi berbagai jenis serangga air sebagai bioindikator pencemaran di DAS Sosongian, Kabupaten Minahasa Selatan. Pengambilan sampel dilakukan dengan menggunakan teknik kick sampling, hand picking, dan sapuan pada tiga stasiun sungai sosongian. Identifikasi serangga air menggunakan kunci identifikasi McCafferty (1981); Morse et al (1994); Yule & Hoi sen (2004); Nebois (1991); Carver (1991).  Hasil penelitian ditemukan sebanyak enam ordo dan 21 famili serangga air. Kata Kunci: Inventarisasi, Serangga Air, Bioindikator Pencemaran